Spanish Port Policy and Management: A Historical and Comprehensive Perspective - González-Laxe, Fernando; Jiménez Sánchez, Fernando (Journal Studies of Public Policy, 2024)
Spanish port policy has undergone significant transformations since the late 20th century, highlighting its shift toward economic competitiveness and the adoption of a landlord model. This model integrates public ownership of infrastructure with private service provision and increased public regulation. The article examines the heterogeneous economic outcomes of the Port Authorities, emphasizing that these are primarily influenced by geographical location, technical specialization, connectivity, and integration into global supply chains rather than the investments made. Additionally, the percentage of concessioned surface area impacts business performance and reinforces the leadership role of ports in their respective hinterlands. These dynamics underscore the influence of globalization and the critical role of public-private collaboration in the port sector.